1983
DOI: 10.1073/pnas.80.3.878
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of parathyroid secretory protein.

Abstract: The phosphorylation ofproteins released into the medium of bovine-parathyroid gland slices or isolated cells incubated with 32Pi has been investigated. The primary protein phosphorylated had a Mr of68,000 and coeluted with newly synthesized parathyroid secretory protein (PSP) on Bio-Gel chromatography and on polyacrylamide gel electrophoresis, Isoelectric focusing of double-labeled samples ([asSimethionine and 32P;) revealed comigration of the two radioactive markers at a pH of.4.6, which was similar to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…6A), the phosphate in all three proteins being predominantly bound to serine residues and to a small extent to threonine, but not to tyrosine, residues (data not shown). The phosphorylation of chromogranin A confirms previous results by others (4,40).…”
Section: Secretogranin I Secretogranin Ii and Chromogranin A Are Phsupporting
confidence: 92%
“…6A), the phosphate in all three proteins being predominantly bound to serine residues and to a small extent to threonine, but not to tyrosine, residues (data not shown). The phosphorylation of chromogranin A confirms previous results by others (4,40).…”
Section: Secretogranin I Secretogranin Ii and Chromogranin A Are Phsupporting
confidence: 92%
“…CGA is known to be phosphorylated at multiple sites [14][15][16]. In the present study we have identified one of these sites as the region giving rise to the active peptide pancreastatin and another in the sequence immediately C-terminal to pancreastatin.…”
Section: Discussionmentioning
confidence: 64%
“…We were able to characterize some of these variants as corresponding to the products of two different cDNA sequences which have previously been reported [6][7][8]. It is known that, during biosynthesis, CGA is also modified by phosphorylation, sulphation and glycosylation [2,[14][15][16][17][18]. However, the precise sites at which these modifications occur are not CGA The specificity of antibodies used in the present study is shown: antibody L300 reacts with peptides having an exposed C-terminus corresponding to CGA(306-313); antibody L331 reacts with the amidated C-terminus of bovine pancreastatin.…”
Section: Introductionmentioning
confidence: 84%
“…Phosphorylation of proteins in some systems has been related to hormone secretion or synthesis (25). We previously reported that phosphorylation of parathyroid secretory protein was inversely proportional to calcium concentration (26), suggesting that this protein could be a substrate for protein kinase C. Finally, there is evidence that protein kinase C systems are linked through guanine nucleotide regulatory proteins (G proteins) to membrane receptors (27). In a recent study, Fitzpatrick et al (28) showed that pertussis toxin (which inactivates G proteins) prevents inhibition by calcium of PTH release.…”
Section: Resultsmentioning
confidence: 99%